INTEGRATION OF HISTORICAL-CULTURAL AND GEOLOGICAL HERITAGE: GEOTRAIL IN THE HISTORIC CENTER OF PORTO ALEGRE, RS - Brito da Silva, Vitoria; Muller Mohr, Ingrid; Canals Meucci, Marcelo; Germano Hilgert, Vinicius; Philipp, Ruy Paulo; fernandes de lima, evandro; Menegat, Rualdo; goulart rodrigues, amanda; Lizzoni Michelin, Cassiana Roberta (Boletim Paranaense de Geociências, 2025)
Geotourism is a form of tourism that uses geology as its main attraction, promoting the preservation of geodiversity and the appreciation of geological and cultural heritage. In urban settings, it connects the history of city development to the materials used in monuments and buildings. Porto Alegre, the capital of Rio Grande do Sul, stands as a true open-air architectural museum, with local rocks incorporated into its Historic Center. This study proposes the creation of a geotrail to highlight the use of rocks in urban development through the analysis of historical buildings and monuments such as the Palácio Piratini, Júlio de Castilhos Museum, Catedral Metropolitana de Porto Alegre, Praça Matriz, Praça da Alfândega, and Farol Santander. The main regional materials identified include Ponta Grossa and Viamão granites, rhyolites, diabases, and sandstones from the Botucatu Formation. Jurassic limestones from France and marbles from Espírito Santo were also used. The macroscopic description of the rocks, combined with historical and architectural context, seeks to promote the integration of geology, culture, and society, reinforcing the importance of preserving Porto Alegre’s historical and geological heritage. Keywords: Geotourism; Historical Heritage; Petrology; Conservation; Geology Education.